2012
DOI: 10.1097/ccm.0b013e318265680a
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory toxicity of buprenorphine results from the blockage of P-glycoprotein-mediated efflux of norbuprenorphine at the blood–brain barrier in mice

Abstract: P-glycoprotein plays a key-protective role in buprenorphine-related respiratory effects, by allowing norbuprenorphine efflux at the blood-brain barrier. Our findings suggest a major role for drug-drug interactions that lead to P-glycoprotein inhibition in buprenorphine-associated fatalities and respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…P-gp has been described as a significant determinant of norbuprenorphine brain exposure and antinocicpetion [21]. Efflux of norbuprenorphine via P-gp may be important to prevent respiratory sedation caused by norbuprenorphine [21,2426]. One recent study has shown that buprenorphine, due to its higher binding affinity and prolonged receptor occupancy, has a protective effect on the respiratory depressive effect of norbuprenorphine [26].…”
Section: Overview Of Drug Dispositionmentioning
confidence: 99%
“…P-gp has been described as a significant determinant of norbuprenorphine brain exposure and antinocicpetion [21]. Efflux of norbuprenorphine via P-gp may be important to prevent respiratory sedation caused by norbuprenorphine [21,2426]. One recent study has shown that buprenorphine, due to its higher binding affinity and prolonged receptor occupancy, has a protective effect on the respiratory depressive effect of norbuprenorphine [26].…”
Section: Overview Of Drug Dispositionmentioning
confidence: 99%
“…Buprenorphine and its metabolite norbuprenorphine are known to affect P-gp at the BBB. 20 In our previous study, sham and jTBI groups both received buprenorphine and jTBI animals showed a difference in the level of P-gp expression. 4 It is therefore very unlikely that a single injection 6 months before would have any effect on P-gp levels by itself.…”
Section: Juvenile Traumatic Brain Injury Modelmentioning
confidence: 99%
“…Administration of the P-gp inhibitor PSC833 in mice was found to significantly increase the respiratory depressive effects of buprenorphine and norbuprenorphine, as well as significantly increase plasma concentrations and reduce brain efflux of norbuprenorphine. Similar effects were also seen in P-gp knock-out mice, suggesting that P-gp plays an important role in the BBB disposition of norbuprenorphine, and that its inhibition can lead to major respiratory side effects (169). A follow up study by the same group found no differences in P-gp mediated BBB transport of buprenorphine or norbuprenoprhine among different strains and genders of mice, despite their variable buprenorphine-induced respiratory toxicities (235).…”
Section: Buprenorphinementioning
confidence: 72%